SIMULTANEOUS INTERPRETING STRATEGIES FOR TRANSLATING FACEBOOK CEO’S INTERVIEW ON HBO’S AXIOS FROM ENGLISH TO INDONESIAN - Okta Viani Dwi Lestari; Ramadan Adianto Budiman (PT Akselerasi Karya Mandiri, 2024)
This study analyzes simultaneous translation strategies in Facebook CEO Mark Zuckerberg’s interview on Axios HBO from English to Indonesian. Using a descriptive qualitative approach, this study identifies various strategies applied by the interpreter, including paraphrasing, transposition, explication, adaptation, and modulation. Data collection methods include literature study, note-taking, reading, and observation, while data analysis utilizes Gile’s Simultaneous Interpretation theory and Kopczynski’s strategies. The results show that the success of simultaneous translation depends not only on linguistic ability but also on the understanding of technology and contemporary social issues, as well as the ability to manage technical terms and political nuances. This research contributes to the field of simultaneous translation studies in the context of technology and media. This research provides insights into practical approaches for interpreters in media settings, with broader implications for simultaneous interpretation in technology-related contexts.